Medication adherence and adverse drug reactions of isoniazid preventive therapy for tuberculosis in people living with HIV (PLHIV) in a tertiary care teaching hospital, Kakinada - M Mani Kruthika; Kandavalli Sri Devi; K V Siva Prasad; Pilla S. Surya Durga Devi (Journal of the Scientific Society, 2023)
Introduction: Human immunodeficiency virus (HIV) and tuberculosis (TB) have a synergistic effect. Suppression of the immune system by HIV increases the risk for TB infection in people living with HIV (PLHIV). It is known for many years that isoniazid 300 mg for a period of 6 months is given for the prevention of TB. Aim: The present study is a prospective study to assess adverse drug reaction (ADR) and patient adherence to isoniazid in HIV patients on antiretroviral therapy (ART). Subjects and Methods: A prospective observational study was carried out for a period of 2 months, i.e., January 2021 and February 2021, in the department of ART at a tertiary care teaching hospital, Kakinada. This study was approved by the institutional ethics committee. The adherence to Isoniazid Preventive Therapy (IPT) was assessed using Morisky Medication Adherence Scale, and all the ADRs reported were assessed for clinical pattern, causality, severity, and preventability. Results: Out of 122 reports, a total of 37 reactions occurred in 24 people. Rash and itching are the majorly reported ADRs, followed by headache and giddiness. According to the WHO causality assessment scale, 21 (87.5%) of the reported cases were probable and 3 (12.5%) were possibly related to suspected medication. Major ADRs were mild (91.6%) according to the severity assessment done by Modified Hartwig and Siegel Scale. Conclusions: Medication adherence is good (61.4%) in the majority of the population (PLHIV), in spite of mild ADRs. The majority of ADRs are mild in nature and the necessity for dechallenge did not arise. Most of the ADRs come under probable, and the majority of them are preventable by proper periodic assessment.